Didyma, Türkei: Site Managment - Bumke, Helga; von Gaisberg, Elgin (e-Forschungsberichte des DAI, 2023)
The work of the Site Management Project in Didyma based on a concept, which was developed 2012 and 2013 and pursues two main objectives. First of all it implies the construction of a new guided tour of the ancient ruins of Didyma, which includes the archaeological site of the sacred way, inaccessible and not visible before, and on the other hand the numerous architectural members, deposited systematically in the area of the Apollontemple during its excavation (1906–1913) for purposes of study (ancient architecture). Furthermore on the basis of injury analysis and damage mapping a scientific concept was developed for the restoration of the collapsed or in danger of collapsing sections of the enclosing wall of the temple area.